The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0004-27492011000500011
|View full text |Cite
|
Sign up to set email alerts
|

Análise discriminante dos pacientes portadores de glaucoma primário de ângulo aberto através do exame de Doppler colorido e do campo visual

Abstract: Editorial Note: After completing the confidential analysis of the manuscript, ABO discloses, with her agreement, the name Dr. Ruth Rosenhek Schor as a reviewer. We thank her effort and expertise in participating in this process. RESUMOObjetivo: Determinar se as variáveis obtidas com exame Doppler colorido associadas às de campo visual são capazes de discriminar olhos normais de olhos glaucomatosos. Métodos: Foram avaliados prospectivamente 36 pacientes portadores de glaucoma primário de ângulo aberto em uso de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many authors have reported that decreased choroidal flow can result in photoreceptor dysfunction, death, 6 glaucoma, 33 and increased severity of AMD. [7][8][9][10][11][12] However, some authors have speculated about a relationship between abnormal choroidal circulation that leads to increased CT and diseases such as in Vogt-Koyanagi-Harada, 13 central serous chorioretinopathy, 2 and others.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that decreased choroidal flow can result in photoreceptor dysfunction, death, 6 glaucoma, 33 and increased severity of AMD. [7][8][9][10][11][12] However, some authors have speculated about a relationship between abnormal choroidal circulation that leads to increased CT and diseases such as in Vogt-Koyanagi-Harada, 13 central serous chorioretinopathy, 2 and others.…”
Section: Discussionmentioning
confidence: 99%